Через тернии - к звездам: роман - Езерская Елена (Русский сериал, 2005)
Экземпляры: аб. (20161027) / Инвентарный номер: 57133 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Е 42 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44